2023
DOI: 10.21203/rs.3.rs-2226827/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognitive–Exercise Dual-Task Intervention Ameliorates Cognitive Decline in Natural Aging Rats via Regulating lncRNA NEAT1/miR-124-3p/caveolin-1-PI3K/Akt/GSK3β Pathway

Abstract: Background: Aging induces degenerative changes in the body and causes cognitive dysfunction, which has a significant negative impact on the daily lives of older adults. At present, there are limited effective interventions to slow the incidence of Aging-related cognitive impairment or even dementia. Among them, exercise and cognitive training are worthy of further research, especially the research on mechanisms. Studies have shown that LncRNA and miRNA play an important role in the occurrence, development, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Exercise training might attenuate hypoxia‐induced apoptosis and axonal growth capacity impairment through the release of miR‐126‐rich circulating endothelial progenitor cell‐derived exosomes (Wang et al., 2020). Moreover, exercise training further protects against MCAO‐induced neurological dysfunction by attenuating apoptotic cell death through activation of the PI3K/Akt/FoxO1 signaling pathway (Li, Tao, et al., 2023). Wang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise training might attenuate hypoxia‐induced apoptosis and axonal growth capacity impairment through the release of miR‐126‐rich circulating endothelial progenitor cell‐derived exosomes (Wang et al., 2020). Moreover, exercise training further protects against MCAO‐induced neurological dysfunction by attenuating apoptotic cell death through activation of the PI3K/Akt/FoxO1 signaling pathway (Li, Tao, et al., 2023). Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wang et al demonstrated that activation of Akt was engaged in the protection of exercise training against neuronal damage induced by CCI.Exercise training might attenuate hypoxia-induced apoptosis and axonal growth capacity impairment through the release of miR-126-rich circulating endothelial progenitor cell-derived exosomes(Wang et al, 2020). Moreover, exercise training further protects against MCAO-induced neurological dysfunction by attenuating apoptotic cell death through activation of the PI3K/Akt/FoxO1 signaling pathway(Li, Tao, et al, 2023). Wang et al also provide evidence that the role of exercise training in neurological injury is related to PI3K/Akt-GLT-1-Glutamat activation after CCI(Wang et al, 2014).…”
mentioning
confidence: 99%
“…The deterioration is often an outcome of genetic and epigenetic interference. This is an in silico search-derived hypothesis, on which further evidence can be proved, and based on the protocol an intervention model can be programmed in the future.Early detection of specific miRNAs and modulation of their expression by therapeutic intervention or using antisense oligonucleotide targeting miRNAs3,17,51 can be an analeptic target to decrease the probability of age-associated diseases. Altogether, this hypothesis provides a notion that circulating miRNAs as one of the epigenetic gene expression modulators and impede it can be an effective restorative target in the successful aging process.AUTH O R CO NTR I B UTI O N SMs.…”
mentioning
confidence: 99%